# |3(-2) - 7| - 7 = ?

1. 3 x (-2) = -6
2. (-6)-7 = (-6) + (-7) = -13
3. |-13| = 13 (absolute value of -13)
4. 13-7 = 6.

|-6 -7| - 7 =

|-13| - 7 =

13 -7 =

6
3 times -2 is -6, subtract 7 and you get -13. The absolute value of -13 is 13, and then you subtract the last 7 so the answer is 6.
/(-6)- 7/ -7=
/-13/ -7=
13- 7=
6
|3(-2) - 7| - 7
|-6 - 7| - 7 ...order of operations: multiply
|-13| - 7....order of operations: subtract
13 - 7 .....| = absolute value means make it postive
13 - 7 = 6 ...subtract

|3(-2) - 7| - 7 = 6
|3(-2) - 7| - 7
=|-6-7|-7
=|-13|-7
=13-7
=6
first treat the absolute value bars as parenthesis and work everything inside of them first:

3(-2)-7= (-6)-7= -13

now replace the absolute value bars and the equation now looks like:

l -13 I -7 ( the absolute value of -13 minus 7)

everything inside of an absolute value becomes positive so:

13-7= 6

I-6 - 7I -7
I-13I -7

I-13I = 13

13-7= 6
OKAY those symbols are "absolute value symbols" so
what ever we need to learn about absolute value can be learned here:

http://www.purplemath.com/modules/absolu...

well, in absolute value, any negatives on it should be eliminated , thus making em positive, so:

first:
|-6 -7| - 7 =

then, find its difference... so it's -13
|-13| - 7 =

what I said: change the negatives to positive..
13 -7 =

then do the solution and it's answer is:

=6